2017
DOI: 10.5505/ejm.2017.76588
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Postmenopausal Strontium Ranelate Treatment on Oxidative Stress in Rat Skin Tissue

Abstract: Strontium ranelate is one of the most common post-menopausal osteoporosis medications that have been used in recent years. The effects of strontium ranelate treatment on the free radical-antioxidant balance of the skin have not been fully elucidated. In this study, we investigated the effects of strontium ranelate treatment on oxidative stress parameters in the skin tissue of rats with the experimental osteoporosis model. Total 35 rats were divided to five groups as control group (Group I), oophorectomy group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…The results showed that serum MDA has a high specificity in ROC statistics, which showed the importance of MDA in the prognostic of osteoporosis. The results found were similar to those observed in the study of Berköz et al . (2017) which showed that serum MDA levels were significantly higher in postmenopausal women with osteoporosis than in the healthy controls.…”
Section: Correlation Between Biological Markerssupporting
confidence: 92%
“…The results showed that serum MDA has a high specificity in ROC statistics, which showed the importance of MDA in the prognostic of osteoporosis. The results found were similar to those observed in the study of Berköz et al . (2017) which showed that serum MDA levels were significantly higher in postmenopausal women with osteoporosis than in the healthy controls.…”
Section: Correlation Between Biological Markerssupporting
confidence: 92%